2020
DOI: 10.1108/reps-10-2019-0142
|View full text |Cite
|
Sign up to set email alerts
|

University business incubators as a tool for accelerating entrepreneurship: theoretical perspective

Abstract: Purpose This paper aims to analyze the link between universities and business incubators (BIs) and to determine how students, scientific researchers and entrepreneurs can benefit from this linkage. It creates an environment in which everyone can help the other to put their new ideas, special skills and abilities into new businesses. In other words, the traditional universities’ role has changed and entrepreneurial universities are now needed to redirect new knowledge for economic development through BIs. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 39 publications
2
48
1
5
Order By: Relevance
“…The variable that featured most strongly was that universities should provide incubation units to motivate students in pursuing an entrepreneurial career after their studies. Hassan [47] has found that universities should ensure an effective incubation system, as this has been seen to successfully enhance and promote entrepreneurship for students. Finally, the experts were asked to identify factors that they felt should be included in an entrepreneurial module or curriculum.…”
Section: Resultsmentioning
confidence: 99%
“…The variable that featured most strongly was that universities should provide incubation units to motivate students in pursuing an entrepreneurial career after their studies. Hassan [47] has found that universities should ensure an effective incubation system, as this has been seen to successfully enhance and promote entrepreneurship for students. Finally, the experts were asked to identify factors that they felt should be included in an entrepreneurial module or curriculum.…”
Section: Resultsmentioning
confidence: 99%
“…It is the responsibility of academic institutions and other capacity-building organisations to develop the type and number of graduates that are able to tackle not only today's challenges. In this singular pandemic actuality, we are also seeing the initiation of a pronounced rearrangement of the social and economic order for the path to the next normal following the coronavirus outbreak [39].…”
Section: Agribusiness and Star-upsmentioning
confidence: 99%
“…Kemudian, sangatlah penting bagi Universitas Telkom untuk membekali fakultas dan mahasiswa dengan pola pikir kewirausahaan untuk memahami bisnis dengan menghubungkan bakat dan kebutuhan industri. Korelasi antara industri dengan penelitian dari akademisi dapat menghasilkan pengetahuan dan menciptakan bisnis baru (Hassan, 2020).…”
Section: Mediaunclassified